(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The application of condensed imidazoles derivatives in the clinical practice and their biological activity were investigated. Dependence of the biological activity orientation from the structher and position of substituants in drags based on was shown imidazopyridine.